Ecological, Photocatalytic, Superhydrophobic and Self-Cleaning Asphalt Pavement Surfaces - Segundo, I. Rocha (2019)
The aim of this research is to develop multifunctions on recycled asphalt mixtures for the surface layer of road pavements. Therefore, preliminary research on functionalization has been carried out. Afterwards, the asphalt mixtures were designed and characterized by mechanical and superficial point of views. The next step is the design of the nanomaterials, their application on asphalt mixtures and the characterization from physical, mechanical and superficial behavior.